Intralaboratory development and evaluation of a high-performance liquid chromatography–fluorescence method for detection and quantitation of aflatoxins M1, B1, B2, G1, and G2 in animal liver. (November 2016) - Shao, Dahai; Imerman, Paula M.; Schrunk, Dwayne E.; Ensley, Steve M.; Rumbeiha, Wilson K.
Aflatoxins are potent mycotoxins with effects that include hepatotoxicity, immunosuppression, and suppression of animal growth and production. The etiologic diagnosis of aflatoxicosis, which is largely based on analysis of contaminated feed matrices, has significant disadvantages given the fact that representative feed samples may not be available and feed-based test methods are not confirmatory of an etiologic diagnosis. A tissue-based analytical method for biomarkers of exposure would be valuable for confirmation of aflatoxicosis. We describe in-house development and evaluation of a high-performance liquid chromatographic method with fluorescence detection and precolumn derivatization for determination of aflatoxins M1, B1, B2, G1, and G2 in animal liver. The method demonstrates good selectivity for the tested aflatoxins in the liver matrix. The overall range was 0.03–0.10 ng/g for limit of detection and 0.09–0.18 ng/g for limit of quantitation. The correlation coefficient ( R 2 ) of calibration curves was >0.9978 for AFM1, 0.9995 for AFB1, 0.9986 for AFB2, 0.9983 for AFG1, and 0.9980 for AFG2 . For fortification levels of 0.2–10 ng/g, repeatability was 10–18% for AFM1, 7–14% for AFB1, 5–14% for AFB2, 6–16% for AFG1, and 10–15% for AFG2 . Recovery was 52–57% for AFM1, 54–62% for AFB1, 55–61% for AFB2, 57–67% for AFG1, and 61–65% for AFG2 . There was no liver matrix effect found. The method is rugged against minor changes based on the selected factors. The results indicate that the proposed method is suitable for quantitative determination of aflatoxins M1, B1, B2, G1, and G2 in liver.